Pengaruh Komunikasi dan Motivasi Belajar Terhadap Prokrastinasi Akademik Mahasiswa FMIPA Universitas Sumatera Utara - Azzahra, Fatya (Universitas Muhammadiyah Sumatera Utara, 2024)
Communication can enhance students' awareness and participation in learning activities, as well as assist in time management and task management. Procrastination is the deliberate postponement of desired activities, even though individuals are aware that this delaying behavior can lead to negative consequences. Learning motivation is something that encourages the emergence of learning activities, guiding these activities to achieve desired goals and determining the speed or slowness of the learning process. This study aims to determine the effect of communication and learning motivation on academic procrastination among students of the Faculty of Mathematics and Natural Sciences at the University of Sumatera Utara. The research method used is a correlational quantitative study with a sample size of 56 respondents selected using incidental sampling techniques. The data obtained were analyzed using SPSS version 29. The results show that: (1) There is a simultaneous effect of communication and learning motivation on academic procrastination among students, as indicated by the simultaneous calculation results showing that the calculated F value (3.605) is greater than the F table value (3.17). (2) Based on partial calculations or T tests, the conclusions are as follows: Ha1 is rejected, Ho2 is rejected, H03 is rejected, and Ho1 is accepted; Ha2 is accepted, Ha3 is accepted. Therefore, communication does not have an effect on academic procrastination among students, while learning motivation has an effect on academic procrastination among students of the Faculty of Mathematics and Natural Sciences at the University of Sumatera Utara.